Assessment of the safety of antimalarial drug use during early pregnancy (ASAP): protocol for a multicenter prospective cohort study in Burkina Faso, Kenya and Mozambique. Issue 1 (December 2015) - Tinto, Halidou; Sevene, Esperança; Dellicour, Stephanie; Calip, Gregory; d'Alessandro, Umberto; Macete, Eusébio; Nakanabo-Diallo, Seydou; Kazienga, Adama; Valea, Innocent; Sorgho, Hermann; Valá, Anifa; Augusto, Orvalho; et al.
Abstract Background A major unresolved safety concern for malaria case management is the use of artemisinin combination therapies (ACTs) in the first trimester of pregnancy. There is a need for human data to inform policy makers and treatment guidelines on the safety of artemisinin combination therapies (ACT) when used during early pregnancy. Methods The overall goal of this paper is to describe the methods and implementation of a study aimed at developing surveillance systems for identifying exposures to antimalarials during early pregnancy and for monitoring pregnancy outcomes using health and demographic surveillance platforms. This was a multi-center prospective observational cohort study involving women at health and demographic surveillance sites in three countries in Africa: Burkina Faso, Kenya and Mozambique [(ClinicalTrials.gov Identifier: NCT01232530)]. The study was designed to identify pregnant women with artemisinin exposure in the first trimester and compare them to: 1) pregnant women without malaria, 2) pregnant women treated for malaria, but exposed to other antimalarials, and 3) pregnant women with malaria and treated with artemisinins in the 2nd or 3rd trimesters from the same settings. Pregnant women were recruited through community-based surveys and attendance at health facilities, including antenatal care clinics and followed until delivery. Data from the three sites will be pooled for analysis at the end of the study. Results are forthcoming. Discussion Despite few limitations, the methods described here are relevant to the development of sustainable pharmacovigilance systems for drugs used by pregnant women in the tropics using health and demographic surveillance sites to prospectively ascertain drug safety in early pregnancy. Trial registration NCT01232530